Development Mathematics Learning Device Based Curriculum 2013 on Subject Quadri Lateral Through Problem Based Learning - Ningsih, Fadriati; Sakur, Sakur; Murni, Atma (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This researchaimed to developmathematics learningdevice that are Lesson Plan (LP) and Students Worksheet (SW) based curriculum 2013 on subjectquadrilateralthrough problem based learning. This research use development model by Borg and Gall.Development is done through the following steps: (1) research and information collecting; (2) planning; (3) develop of product: (4) preliminary field testing; (5) revision; (6) main field testing; and (7) revision. Researcher conducted a needs analysis, then collect the necessary materials to designlearning device. Learning device that had been developed then validated by three validators and revised based on the input from validators. The valid learning device then tested in two stages, the small group trial with subjects are eight students and large group trial with subjects are 29 students. Based on the data analysis obtained that the mathematics learning device are valid with average for LP 3,79 and 3,82 for SW and practical to use by learners.